Cancer patients' diagnosis and symptoms and their family caregivers' self‐efficacy and social support are associated with different caregiver reactions. (4th September 2020) - Astrup, Guro Lindviksmoen; Hofsø, Kristin; Bjordal, Kristin; Rustøen, Tone
Abstract: Objective: To describe caregiver and patient characteristics that are associated with negative and positive reactions in family caregivers (FCs) of cancer outpatients. Methods: A total of 194 FCs completed the Caregiver Reaction Assessment (CRA) scale 6 months after start of new treatment in patients with breast, ovarian, colorectal, or head and neck cancer. Linear regression models were used to examine which caregiver characteristics (i.e. demographic, self‐efficacy and social support) and patient characteristics (i.e. clinical, symptoms) were associated with each of the CRA subscales (caregiver esteem, lack of family support, and impact on health, schedule and finances). Results: Less social support was significantly associated with poorer scores on all subscales (B −0.01/0.01). Also, poorer scores on one or more of the CRA subscales were reported by FCs who had lower self‐efficacy (B −0.02), a higher level of education (primary B 0.42, secondary B 0.22), more medical conditions (B 0.06), and were female (B 0.20), and by FCs of patients with colorectal (B 0.45) or head and neck cancer (B 0.27), and those who reported a higher symptom burden (B 0.28/0.49). Conclusion: Both caregiver and patient factors were associated with reactions in FCs of cancer outpatients. This information can be used by healthcare personnel to identify FCs who need additional support (e.g. counselling), and to increase focus on strengths and assets within the caregivers (e.g. support groups).